If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(X + 7) + -4 = 0 Reorder the terms: 8(7 + X) + -4 = 0 (7 * 8 + X * 8) + -4 = 0 (56 + 8X) + -4 = 0 Reorder the terms: 56 + -4 + 8X = 0 Combine like terms: 56 + -4 = 52 52 + 8X = 0 Solving 52 + 8X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-52' to each side of the equation. 52 + -52 + 8X = 0 + -52 Combine like terms: 52 + -52 = 0 0 + 8X = 0 + -52 8X = 0 + -52 Combine like terms: 0 + -52 = -52 8X = -52 Divide each side by '8'. X = -6.5 Simplifying X = -6.5
| 8x+4=-11 | | 4a+36=29 | | 3x-(-14)=19 | | -54x=-6 | | 4x^2-4x+1=7 | | x+-5sqrt(x)+6=0 | | 5y-9=4y+6 | | y=5-3(-2) | | 2.25x=15.75 | | .60x+.25=.35x-4 | | c=4.95p+32.50 | | x^2-36x+324=1 | | 2(4-0.3b)=6.5 | | 8x-7=x(A+2B)+A-3B | | .25b+.40b-5=-3 | | 4.9(t)+10(t)-5=0 | | 8x+2x-10=100 | | [(x)(x)]-x=2 | | 25h=-15h-80 | | 3/4+x-2=3/5 | | -x+7(x-5)=-32+7x | | 4x-18=10x+8 | | y=5x-2-7 | | 25h=-1h-80 | | [k-5]=4 | | 2x-10=4+x | | 4.9t^2-5t=-12 | | 5.5x+26=5x-10 | | 6+35=21x+30 | | 2a-11=-8a+30 | | x+12=-46 | | 2n*3=48 |